Immunotherapy to Treat Cancer. Issue 3 (September 2016) - McCune, JS
Abstract : This issue of Clinical Pharmacology & Therapeutics focuses on immunotherapy as an approach to treat cancer by generating or augmenting an immune response against it. The enthusiasm for immunotherapy has waxed and waned over the past century. Enthusiasm for immunotherapy has risen over the past decade due, in part, to data showing that cancer immunotherapy consistently improves overall survival in select patients with advanced‐stage cancer. Antitumor immunotherapy has broad potential and could be used to treat many different types of advanced‐stage cancer due to the durable and robust response that it elicits across a diverse spectrum of cancers. This issue covers various aspects of relevant therapeutic topics ranging from discovery of chimeric antigen receptor (CAR) T cells, development of novel immunotherapies using novel pharmacokinetic/dynamic modeling tools, to the utilization of immune checkpoint therapy. Regarding utilization, this issue addresses biomarker selection strategies for personalized treatment of non‐small cell lung cancer (NSCLC) with immune checkpoint therapy and also the management of the unique immune response adverse events (irAEs).